Spectrum of Somatic Malignancy in Testicular Germ Cell Tumors—A Histopathological Review of 25 Cases with Clinical Outcome - Subramanian, Priyadarsani; Arora, Amandeep; Pal, Mahendra; Prakash, Gagan; Maitre, Priyamvada; Murthy, Vedang; Joshi, Amit; Rane, Swapnil; Desai, Sangeeta; Menon, Santosh (Indian Journal of Medical and Paediatric Oncology, 2024)
Introduction Germ cell tumors (GCTs) are the commonest testicular malignancy in young males. These tumors are highly chemoresponsive, however become resistant to conventional therapy when a somatic-type malignancy (SM) develops, which happens in ∼3 to 6% of the cases.Materials and Methods We reviewed the histologic profile of all cases of testicular/retroperitoneal GCT with SM, diagnosed over a period of 12 years in our institute. Correlation of histologic profile with clinical outcome was done wherever feasible.Results A total of 25 cases of testicular/retroperitoneal GCT with SM were identified for review. The histological spectrum of SMs included carcinoma (n = 9), sarcoma (n = 9), embryonic-type neuroectodermal tumor (ENET) (n = 4), and other rare histological types (n = 3). SMs were frequently seen at the resected metastatic sites (n = 13) and in postchemotherapy setting (n = 12); 14 cases had concurrent GCT and SM at the time of diagnosis/initial resection and 9 cases presented as late relapses (more than 2 years after initial presentation). Four patients were treated with metastasectomy and lymph node dissection, six patients were treated with combined resection and chemotherapy, and nine patients were treated with only adjuvant chemotherapy. The patients with SM confined to testis and those treated with multimodality approach had relatively better outcome.Conclusion GCTs with SM are a highly heterogeneous group of tumors with varying histologic types and management strategies. Strict adherence to histological diagnostic criteria, differentiating these tumors from close mimics such as glandular and sarcomatoid yolk sac tumors, teratomatous overgrowth, and a new second primary somatic tumor are important due to implications in management and prognosis.
Keywords: germ cell tumors; somatic malignancy; embryonic-type neuroectodermal tumors; rhabdomyosarcoma; teratomatous overgrowth